2016
DOI: 10.1088/1674-1056/25/2/027103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of electrical and optical characteristics of ZnO/CdS/CIS thin film solar cell

Abstract: In this study, device modeling and simulation are conducted to explain the effects of each layer thickness and temperature on the performance of ZnO/CdS/CIS thin film solar cells. Also, the thicknesses of the CIS and CdS absorber layers are considered in this work theoretically and experimentally. The calculations of solar cell performances are based on the solutions of the well-known three coupling equations: the continuity equation for holes and electrons and the Poisson equation. Our simulated results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Since the band gap E g of chalcopyrite semiconductors covers most of the energy spectra for the visible light (1 eV-3 eV), the maximum absorption of the solar spectrum can be utilized for the energy conversion and cause these chalcopyrites to develop into the possible substrates for the fabrication of optoelectronic devices. [2,[9][10][11][12][13][14][15][16][17] The solar cells based on CuInSe 2 and CuInS 2 have already reached efficiencies of 18.8% and 12%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] Since the band gap E g of chalcopyrite semiconductors covers most of the energy spectra for the visible light (1 eV-3 eV), the maximum absorption of the solar spectrum can be utilized for the energy conversion and cause these chalcopyrites to develop into the possible substrates for the fabrication of optoelectronic devices. [2,[9][10][11][12][13][14][15][16][17] The solar cells based on CuInSe 2 and CuInS 2 have already reached efficiencies of 18.8% and 12%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Since CuInTe 2 is a direct band gap semiconductor, in order to minimize the requirements for minority carrier diffusion lengths, it can be made as either n-or p-type semiconductor with a variety of potentially low-cost homojunction and heterojunction applications as an alternative to monocrystalline and polycrystalline silicon technology. [11,12,16,[18][19][20][21] Some relevant studies have been reported. Gonzalez and Rincón reported the optical absorption and phase transitions of CuInTe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Developing new CQDs materials with wider photoresponse range is one of the most effective ways to further improve QDSCs performance. Ternary or multi-component alloyed CQDs are good choice, which are strongly dependent on the synthetic techniques, such as CuInS 2 , CdSeTe, CuInSe 2 , CuInSe 1−x S x , Zn-Cu-In-Se, CuInTe 2−x Se x , etc, [45,[48][49][50][51][52] as shown in Fig. 2.…”
Section: Cqd Materials For Qdscsmentioning
confidence: 99%
“…Due to their unique characteristics, colloidal quantum dots have attracted extensive interests from both fundamental and applied points of view. [1][2][3][4][5] During the last decade, a new type of solar cells with PbS QDs layer as absorber was developed rapidly and showed many advantages towards future photovoltaics, such as tailored light-harvesting, solution-based deposition technology, and good air stability. [6][7][8][9][10] However, the compromise of light absorption and carrier collection still serves as a big obstacle towards its further improvement.…”
Section: Introductionmentioning
confidence: 99%